Neuromonitoring – still highly controversial - Bryk, Piotr; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2021)
Recurrent laryngeal nerve (RLN) paralysis, although rare, is among the most serious complications of thyroid gland surgery. It effects the quality of life of the patient, increases the costs of hospitalization, and can be the cause of legal proceedings. Therefore, it is not surprising that for a long time, devices have been sought that minimize the risk of injury to the nerves. One of them is intraoperative neuromonitoring (IONM). Despite several decades of using neuromonitoring during thyroid gland surgeries, there is still much controversy concerning its effectiveness. The divergent results of various meta-analyses are probably associated with the lack of standardization and inappropriate use of the method. Indisputable benefits from the use of IONM were proven in high-risk surgeries, such as malignant cancer, overactive thyroid gland, recurrent goitre, or retrosternal goitre. Nerve monitoring can be carried out by intermittent (I-IONM) or continuous (C-IONM) stimulation. At present, increasing importance is attached to continuous monitoring, because it protects the nerve against injury in real time, and the surgeon is warned against performance of a dangerous manoeuvre. Neuromonitoring is safe and does not show undesirable effects. Even though its use increases the costs of surgery and hospitalization, it improves the quality of the procedure and ensures the safety of the patient and the surgeon.